From dairy farming to dairy processing: A story of rural entrepreneurship - Talwar, Gopika; Chawla, Rekha (Indian Farming, 2025)
Dairy farming plays a vital role in strengthening the rural economy by providing farmers with a steady and reliable source of additional income. Along with crop cultivation, dairy has become an important livelihood activity that ensures daily cash flow and financial stability for farming families. By taking a step further into dairy processing, farmers can transform raw milk into value-added products such as curd, paneer and ghee for much higher returns compared to selling liquid milk alone. Processing not only helps in extending shelf-life and reducing spoilage but also enables farmers to build their own brands in local markets. With proper training, technical support, and entrepreneurship development, farmers can acquire skills in processing, packaging, and marketing, becoming self-reliant entrepreneurs. Thus, dairy farming and processing together create a sustainable model that enhances income, employment opportunities, and rural prosperity, making it a powerful tool for empowering the farming community. S. Jasveer Singh, from village Hamidi, district Barnala, is such an examplary to illustrate how scientific guidance, training, and entrepreneurship can transform rural livelihoods.